Tubuh, Rupa, dan Busana: Eksplorasi Body Painting Dayak dalam Tata Rias dan Busana di Pendidikan Sendratasik UPR - Girindraswari, Nawung Asmoro; Aulia Mayangsari, Marrisa; Andis, Muh.; Romadoni, Muhamad; Arie Astuti, Andi (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
Art learning within the Sendratasik Study Program, FKIP, University of Palangka Raya is designed to encourage student creativity with a local wisdom approach. One form of artistic expression developed is body painting, which is not only a means of visual exploration, but also supports the needs of drama, dance, and music performances. This research aims to explore the potential of body painting makeup art as an innovative learning method for Sendratasik students. The method used in this study uses a descriptive method with data collection techniques in the form of observation, literature study, aesthetic experience, and supporting documentation. The results of the study show that body painting works created by students have high aesthetic value and display creativity and innovation in visual form. A variety of visual motifs, such as Dayak ornaments, flora, and fauna are an important part of creating a unique and meaningful art form.